Pipe leak detection and monitoring system using pressure residual method - Abdulshaheed, Ali Mohammed Ali (2016)
The research work utilises "pipe leak monitoring by means of pressure sensors" or "leak detection and localisation using pressure sensors inside a pipe", which refers to an integrated use between the liquid, the sensor, and the PC software. Monitoring pipes is used for leak detection in the pipe, and is performed by using a residual approach which means monitoring the pressure variation inside a water district section (WDS). Sensors show the data that has been accumulated from the liquid inside the pipe. The liquid responds to the leak influence due to hydraulic rules when a drop in the pressure value occurs due to a negative wave pressure phenomenon. Leak detection methods are used to minimise the cost of pipe inspection and reduce the cost of liquid blow out in the pipe due to leak deterioration. In addition, it helps to prevent the disaster of explosions caused by gas seepage or petrol leakage. Early leak detection prevents any influence on the infrastructure around the pipe because of small leaks, which can spill much water over a long period of time. Moreover, it reduces the hazard of epidemic infections when waste water impurities enter inside the distribution system. Many detection approaches have been proposed in the past, but a monitoring distribution system using pressure sensors is preferred, because it does not need to shut down a part of the network. The use of pressure sensors gives a faster response and they are easy to maintain. In addition, the acoustic method has an influence on traffic and it is not effective in plastic material (PVC). The development of the hydraulic model and an hydraulic solution for a water distribution system enhances the ability to represent a fire flow condition in the simulation program. The EPANET program is the result of advanced research and it would be able to simulate fire flow (leak or deficiency condition) in the water distribution system. The pressure exponent in the hydraulic equation was used as a fixed value equal to 0.5 in the pressure residual approach for detecting and localizing leaks in the water distribution system. Moreover, this study utilizes different pressure exponent that used according to the material type of the network pipes and illustrates the influence on the values of sensitivity matrices. The result showed that the applied different pipe material approach (different exponent value) would enhance the result of the sensitivity matrix which is considered as a leak detection layer in the pressure residual method. Monitoring experiments have been performed in Malaysia, at the Selangor Seri Aman water district section to produce a sensitivity matrix, and examine the effect of different pipe materials (PVC, metallic and Asbestos Cement) and other aspects on the sensitivity matrix value. The ArcMap program was used to reduce the uncertainty of customer distribution density in the EPANET program model node through an account of the base demand parameter.